If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + 3x + 4x = -10 + 6x Combine like terms: 3x + 4x = 7x -4 + 7x = -10 + 6x Solving -4 + 7x = -10 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -4 + 7x + -6x = -10 + 6x + -6x Combine like terms: 7x + -6x = 1x -4 + 1x = -10 + 6x + -6x Combine like terms: 6x + -6x = 0 -4 + 1x = -10 + 0 -4 + 1x = -10 Add '4' to each side of the equation. -4 + 4 + 1x = -10 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = -10 + 4 1x = -10 + 4 Combine like terms: -10 + 4 = -6 1x = -6 Divide each side by '1'. x = -6 Simplifying x = -6
| 8(70-a)+5s=440 | | X^2-85x-1050=0 | | x^5+x^3-2x= | | 17x-8x=9 | | 560-8a+5s=440 | | X-14=-41 | | 6x-7-4x= | | 4-5x=-5-x-5x | | -60=6a | | 150m-75m+52800=55000-200m | | x^4-x^3-3x^2+5x=2 | | 4y+3=3x+17 | | 4z+3z+6=180 | | 12x+24=16x+40 | | y-620=0(x-500) | | 3w+5w=40 | | X+(x+3)+(X-2)=46 | | 2x^4-6x^2-8=0 | | 6-6x=7x-10+3 | | 3/4x-2y=15 | | -7x+5=2x-10.1 | | 2(1-4x)=3(3x+5) | | 3(4x-7)=5(3x+3) | | 4x^2+20=20x | | 30=4.9x^2+15x+30 | | 5x-32-11x=22 | | 8x-17-25x=12x+5x-34 | | 6(2x+4)=4(4x+7) | | a^4-2a^2b^2+b^4= | | 7c/2c | | 7x+(5x+3)=5(x-3)+2 | | 7f=28 |